2000
DOI: 10.1002/(sici)1097-4636(20000315)49:4<506::aid-jbm9>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Use of recombinant human osteogenic protein-1 for the repair of subchondral defects in articular cartilage in goats

Abstract: The objective of this pilot study was to examine in vivo the potential of recombinant human osteogenic protein-1 (rhOP-1, also called bone morphogenetic protein-7, BMP-7) for treatment of subchondral lesions by induction of new hyaline cartilage formation. Subchondral left knee defects in 17 mature goats were treated with fresh coagulated blood mixed with (1) rhOP-1 combined with collagen (OP-1 device, 400 microgram/mL); (2) rhOP-1 alone (OP-1 peptide, 200 microgram/mL); (3) OP-1 device with small particles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…29 In other reported studies, untreated full-thickness defects with diameters of 4 to 10 mm healed with biomechanically inferior fibrous or fibrocartilagenous tissue covering the defect, frequently with fissuring towards its center and, in some examples, cartilage matrix flow covering the defect periphery. [30][31][32][33][34] The outcome in our goats was, by comparison, substantially better. First, the congruency between the surface implant and adjacent cartilage, as well as the device's accurate replication of the articular contour, provided an effective weight-bearing continuum across the MFC, reflected in the generally balanced increase in bone modeling and remodeling noted around the surface and anchoring components of the prostheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In other reported studies, untreated full-thickness defects with diameters of 4 to 10 mm healed with biomechanically inferior fibrous or fibrocartilagenous tissue covering the defect, frequently with fissuring towards its center and, in some examples, cartilage matrix flow covering the defect periphery. [30][31][32][33][34] The outcome in our goats was, by comparison, substantially better. First, the congruency between the surface implant and adjacent cartilage, as well as the device's accurate replication of the articular contour, provided an effective weight-bearing continuum across the MFC, reflected in the generally balanced increase in bone modeling and remodeling noted around the surface and anchoring components of the prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Although focal articular changes were documented in operated joints, the pathology was much reduced over that encountered in previous caprine osteochondral defect studies. [30][31][32][33][34] Expanded preclinical or clinical human studies are justified.…”
Section: Discussionmentioning
confidence: 99%
“…This dosage was the same as that used in the study by Johnstone et al [17], which reported an increase in growth plate height adjacent to the defect. This dosage is within the range of that used in other in vivo studies to regenerate articular and thyroid cartilages, doses of which have ranged from 11 pg to 500 pg f4, 16,18,24]. All of these studies have reported an induction of chondrogenesis, with cells taking on the chondrocyte phenotype and producing cartilage specific collagens and proteoglycans.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to its powerful bone healing properties, the chondrogenic potential of OP-1 has been 0736 well documented [3,4,6,11,15,16,24]. In vitro studies in rat calvarial cells, ATDC5 cells, mouse embryonic long bone cultures, transplanted perichondrial cultures and articular cartilage cultures have reported an increase in the synthesis of type I1 collagen and proteoglycans following the administration of recombinant human OP-1 (rhOP-I); [l-3,5,6,13,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation